Unincorporated Merchant: How Does the Law Protect Consumers in Electronic Commerce? - Andika Prawira Buana; Rashid Ating; Tri Abriana Ma'ruf (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2023)
Currently, electronic commerce (e-commerce) is a platform that allows merchants and consumers to easily conduct online transactions. Nonetheless, there are a lot of e-commerce business actors who do not yet have legal entity status. The purpose of this research is to discover and examine rules pertaining to e-commerce merchants who are not incorporated, as well as what portions of consumer legal protection are available to consumers. This doctrinal legal research uses statutory and conceptual approaches. The results of the study show that regulatory provisions for e-commerce business actors who are required to be legal entities (incorporated) have been contained in regulations issued by the Minister of Trade, while e-commerce business actors who are not legal entities are regulated in various regulations such as the Law on Electronic Information and Transactions, the Consumer Protection Act, and the Trade Quiet Act. However, the regulation does not explicitly contain e-commerce obligations for legal entities. In fact, the legality of business actors is highly recommended because it guarantees legal protection for consumers if they experience losses in the future. In addition, it is also a potential source of income for countries with tax schemes. Based on this, it is suggested that the government immediately draw up specific regulations so that every e-commerce business actor is not given any other choice but to have a legal entity. It is also necessary to stipulate strict sanctions against unincorporated business actors and result in losses to consumers.